Inactivation of microglial LXRβ in early postnatal mice impairs microglia homeostasis and causes long-lasting cognitive dysfunction - Keyi Lv; Yi Luo; Tianyao Liu; Meiling Xia; Hong Gong; Dandan Zhang; Xuan Chen; Xin Jiang; Yulong Liu; Jiayin Liu; Yulong Cai; Per Antonson; et al. (Proceedings of the National Academy of Sciences, 2025)
Microglia, the largest population of brain immune cells, play an essential role in regulating neuroinflammation by removing foreign materials and debris and in cognition by pruning synapses. Since liver X receptor β (LXRβ) has been identified as a regulator of microglial homeostasis, this study examined whether its removal from microglia affects neuroinflammation and cognitive function. We used a cell-specific tamoxifen-inducible Cre-loxP-mediated recombination to remove LXRβ from microglia specifically. We now report that ablation of LXRβ in microglia in early postnatal life led to a reduction in microglial numbers, distinct morphological changes indicative of microglial activation, and enhanced synapse engulfment accompanied by cognitive deficits. Removal of LXRβ from microglia in adult mice caused no cognitive defects. RNAseq analysis of microglia revealed that loss of LXRβ led to reduced expression of SAll1, a master regulator of microglial homeostasis, while increasing expression of genes associated with microglial activation and CNS disease. This study demonstrates distinctly different functions of microglial LXRβ in developing and adult mice and points to long-term consequences of defective LXRβ signaling in microglia in early life.